Citogenética e palinologia das subfamílias Caesalpinioideae e Faboideae (Fabaceae) do Sul de Minas Gerais - Ferreira, Kátia (2009)
Fabaceae, the third largest family of flowering plants, has its centers of diversity in tropical and subtropical regions and is divided in three major groups: Caesalpinioideae, Mimosoideae and Faboideae. Faboideae, considered as monophyletic and derived from subfamily Caesalpinioideae, includes the genus Crotalaria. This genus is important in industry of paper and cellulose, in agriculture as nitrogen fixer, as animal feed and as biological control of nematodes, in heavy metal bioremediation and in landscaping. Caesalpinioideae considered paraphyletic, includes the genera Peltophorum, Cassia sensu stricto and Senna. The last one have great potential for medicinal, ornamental, wood and degraded areas restoration. The genera Cassia sensu stricto, Senna Mill. and Chamaecrista Moench. make up the complex genus Cassia sensu lato. Cassia s.l. is considered multibasic, having x=7 as the primary basic chromosome number from which secondary basic number x=14 has been established. The basic numbers x = 13 and 12 might have evolved through aneuploidy reduction. It is controversial wheter x= 7 or x= 8 is the basic number of Crotalaria genus. The phylogenetic relationships in all taxonomic levels of Fabaceae family are not well explained yet, lacking new models based on information other than the morphologic ones. Description of chromosome number, meiotic behavior, pollen grain viability and morphology is showed for species of the subfamilies Caesalpinioideae and Faboideae from South Minas Gerais. Most of the Senna species showed regular meiotic behavior and high meiotic index and pollen grain viability. Basic number of the genus is discussed, taken in account disploidy and autopolyploidization along the evolution process of Senna. The Crotalaria species showed abnormal meiotic behavior, with typical abnormality for each species, resulting in low pollen grain viability. Pollen data showed variability useful for phylogenetic analysis. The consensus tree unrevealed low consistency in Senna grouping.